Pengujian Efisiesni Pasar Bentuk Setengah Kuat Secara Keputusan: Analisis Pengumuman Dividen Meningkat - Doddy Setiawan; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
This research aims at examining the decisionally efficient market by analyzing dividend increase announcement at Jakarta Stock Exchange. The analysis includes three aspects: information content, speed of market reaction and accuracy of market reaction.The sample for this research is 132 firms during the period of 1992-1996. The analysis shows that on the announcement date market significantly gave positive reaction to dividend increase announcement. This reaction resulted in abnormal return of 0,3838%. This fact shows that the dividend increase announcement in Indonesia has an information content and market react quickly. To analyze the accuracy of market reaction, the sample is divided into 2 parts: growth and non-growth firms. The analysis then shows that market did not react significantly to growth firms and gave positive reaction to non-growth firms. Actually, market should give positive reaction to the growth firms only and negative reaction to the non-growth firms. Finally, the conclusion is that Jakarta Stock Exchange is not a decisionally efficient market.